Banking Customer Loyalty: Unveiling the Role of Customer Relationship Marketing and Customer Value - Azhari, Azlan; Utari, Nur (Advances in Business & Industrial Marketing Research, 2023)
Purpose: This research explores the influence of Customer Relationship Marketing (CRM) and customer value on customer loyalty at Bank BRI. The study examines how customer satisfaction mediates these relationships and assesses the moderating effects of demographic factors such as age, gender, and education level on loyalty. The research hypothesizes that effective CRM and enhanced customer value lead to increased customer loyalty through higher satisfaction and perceived value. Research Design and Methodology: The study adopts a quantitative research design, utilizing surveys to gather data from 400 customers across multiple branches of Bank BRI in Indonesia. Multiple linear regression and path analysis are employed to analyze the data, focusing on the relationships between CRM, customer value, and loyalty. The sample is selected using stratified random sampling to ensure a representative cross-section of Bank BRI’s diverse customer base. Findings and Discussion: The findings reveal that CRM and customer value significantly impact customer loyalty, explaining 78.7% of its variance. CRM enhances loyalty through improved customer satisfaction and perceived value, while demographic factors such as age and education level moderate this relationship. The study underscores the critical role of personalized communication, digital innovation, and robust data security in cultivating customer loyalty. Implications: The research provides valuable insights for bank managers to refine their CRM strategies, emphasizing the importance of personalized and secure customer experiences. The study suggests further research to explore other factors, such as digital engagement and competitive market dynamics, to deepen the understanding of customer loyalty in the banking sector.